Exploring the relationship between metacognition and motivation in Peruvian basic education students - Yancachajlla-Quispe , Luis Iván; Rengifo-Ramírez , Sheyla Shericza; Farfán-Latorre , Marilú; Estrada-Araoz , Edwin Gustavo; Lavilla-Condori , Willian Gerardo; Lavilla-Condori , Mari Luz (Salud, Ciencia y Tecnología - Serie de Conferencias, 2024)
Introduction: Metacognition is essential in the teaching-learning process, as students who are aware of their own thinking processes tend to be more effective in acquiring knowledge and skills.Objective: To determine if there is a relationship between metacognition and motivation in Peruvian basic education students.Methods: Quantitative research, non-experimental design with correlational scope. The sample consisted of 130 students who responded to two questionnaires characterized by adequate metric properties.Results: Preliminarily, it was found that students applied metacognitive processes efficiently and their level of motivation was high. On the other hand, it was determined that the Kendall's Tau b correlation coefficient for both variables was equal to 0.501 and the p-value was lower than the significance level (p